Policy Implementation in Management of Anchor Harbors Kepulauan Riau Province - Ardiansyah, Achmad; Samin, Rumzi; Adhayanto, Oksep (Metta : Jurnal Ilmu Multidisiplin, 2024)
Research discusses the implementation of anchor anchor management policies in the Kepulauan Riau Province which involves various actors with different interests. Research objectives are to implement anchor anchor management policies in the Kepulauan Riau Province. Research method used is a post-positivism approach by analyzing the types of benefits obtained, the scale of change desired, the decision-making framework, institutional and regime characteristics, as well as policy implementation and responsiveness. Results and discussion show that implementing this policy has significant economic, social, environmental and security benefits but still requires improvements to infrastructure and supporting facilities. There is also a need for good cooperation and coordination, increasing institutional capacity, increasing the capabilities of relevant officials, as well as developing technology and innovation to support more effective policy implementation. In conclusion, the anchor anchor management policy in the Kepulauan Riau Province must be improved so that it can have a positive impact on the community and the surrounding environment and improve the welfare of the local community. Apart from that, this research also highlights the importance of involving various actors in decision making regarding anchor anchor management policies. In this way, the resulting policies can be more effective and efficient, and can meet the needs and interests of all parties involved. Implication of this research is the need for synergy and collaboration between various actors regarding anchor anchor management policies. Apart from that, it is also important to pay attention to the decision-making framework, characteristics of institutions and regimes, as well as policy implementation.